Le journal Le Pays et la guerre de Sécession (1861-1865) - Fortin, Philippe (Université du Québec à Montréal, 2000)
Keywords: Guerre

La perception de la guerre civile américaine dans la presse québécoise, 1861-1865 - Jacob, François (Université Laval, 2010)
Keywords: Guerre

Les Pointeliers en guerre - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Armée; Guerre; Milice; Pointe-aux-Trembles; Quartiers

La guerre de 1812: Journal de Jacques Viger - Viger, Jacques; Andrès, Bernard (Les Presses de l'Université Laval, 2012)
Keywords: Maires; Viger; Jacques

Le triomphe de l’opéra italien à Montréal, de l’union des Canadas à la Grande Guerre - Barrière, Mireille (Cap-aux-Diamants, 2016)
issued: 2016-23-00
Keywords: Opéra; Théâtre Royal

Le Roi, l'Église et la guerre: la prédication à Montréal au moment de la conquête (1750-1766) - Décary, Simon (Université de Montréal, 2008)
Keywords: Communautés religieuses; Sulpiciens

La culture médiatique francophone en Europe et en Amérique du Nord. De 1760 à la veille de la Seconde Guerre mondiale - Pinson, Guillaume (Les Presses de l'Université Laval, 2016)

Vapeur, thermoélectricité et hydroélectricité comme force motrice le long du corridor industriel du canal de Lachine, des années 1850 à la Seconde Guerre mondiale - Gelly, Alain (Université Laval, 2010)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

An Examination of the Coverage of the War of 1812 in the Montreal Gazette, 1812-1815 - Perrone, Julie (Canadian Issues, 2012)
issued: 2012-23-00
Keywords: Guerre; Montreal Gazette

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Number: 75
Keywords: Guerre; Lachine; Émeutes

The Surrender of Montreal to General Amherst de Francis Hayman et l'identité impériale britannique - Turcot, Laurent (Mens, 2011)
issued: 2011-23-00
Keywords: Capitulation; Guerre; Peinture

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (University of British Columbia Press, 2006)
Keywords: Guerre; Quartiers; Verdun

With Thought and Faith: Henri Bourassa and the Great War - Keelan, Geoff (Worth Fighting For: Canada’s Tradition of War Resistance from 1812 to the War on Terror, 2015)
Keywords: Bourassa; Henri; Devoir (Le); Guerre

Louis-Joseph Papineau. Les débuts, 1808-1815 - Ostiguy, Raymond; Aubin, Georges (Éditions Histoire Québec, 2015)
Keywords: Avocats; Députés; Guerre; Milice; Papineau; Louis-Joseph

150 ans d’histoire militaire au centre-ville de Montréal - Joly, Diane (Revue militaire canadienne, 2016)
issued: 2016-24-00
Keywords: Dominion (square); Guerre; Monuments; Places publiques; Squares

Lacorne Saint-Luc: l'odyssée d'un noble, 1711-1784 - Saint-Pierre, Marjolaine (Septentrion, 2013)
Keywords: Fourrure; Guerre; La Corne; Luc de (La Corne Saint-Luc ou Saint-Luc de La Corne); Marchands; Noblesse